2017
DOI: 10.1007/s00240-017-0998-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomised Phase II/III study to evaluate the efficacy and safety of orally administered Oxalobacter formigenes to treat primary hyperoxaluria

Abstract: Primary hyperoxaluria (PH) patients overproduce oxalate because of rare genetic errors in glyoxylate metabolism. Recurrent urolithiasis and/or progressive nephrocalcinosis are PH hallmarks and can lead to kidney damage, systemic oxalosis and death. Based on previous studies, we hypothesised that treatment with the oxalate-metabolizing bacterium Oxalobacter formigenes would mediate active elimination of oxalate from the plasma to the intestine of PH patients, thereby reducing urinary oxalate excretion (Uox). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 33 publications
2
53
0
1
Order By: Relevance
“…Despite maintaining of an ecosystem the colonization of Oxalobacter formigenes inside the human gut as healthy gut flora 10 describing the withholds host health features and other core microbiome as well 9 . As their absence corresponds to enhanced level of oxalate in systemic fluid 49 , replacement therapy granted the recovery from hyperoxaluria condition in humans 50 . Demonstrating the colonization status of Oxalobacter formigenes , we speculate the major role of this bacterium in settlement of functional eubacteria and trans-domain species as well as in symptomatic phase of hyperoxaluria i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Despite maintaining of an ecosystem the colonization of Oxalobacter formigenes inside the human gut as healthy gut flora 10 describing the withholds host health features and other core microbiome as well 9 . As their absence corresponds to enhanced level of oxalate in systemic fluid 49 , replacement therapy granted the recovery from hyperoxaluria condition in humans 50 . Demonstrating the colonization status of Oxalobacter formigenes , we speculate the major role of this bacterium in settlement of functional eubacteria and trans-domain species as well as in symptomatic phase of hyperoxaluria i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Primary hyperoxaluria describes a group of inborn errors of metabolism where defective liver enzymes involved in glyoxylate metabolism result in excess production of oxalate [49]. The predominant route of oxalate excretion is via the kidneys, with enteric excretion also playing a role when renal function is impaired [50]. In primary hyperoxaluria, excessive oxalate levels supersaturate renal excretion mechanisms, leading initially to calcium oxalate deposition within the kidney, and subsequently systemic oxalosis (deposition of oxalate within other systems) affecting the skeleton, heart, liver and other organs [49].…”
Section: Primary Hyperoxaluriamentioning
confidence: 99%
“…The evolution of our treatment of this condition therefore hinges upon identifying therapeutic targets which do not necessitate organ transplantation to replace the defective enzyme. Trials utilising the oxalate-metabolising bacterium Oxabacter formigenes to increase gut excretion of oxalate and reduce urinary oxalate excretion reached phase II/III trials but did not significantly reduce urinary oxalate excretion [50]. Animal studies have shown oxalate decarboxylase enzymes can effectively reduce urinary oxalate levels, providing an alternative potential future therapy for reduction of calcium-oxalate nephrocalcinosis in primary hyperoxaluria [53,54].…”
Section: Primary Hyperoxaluriamentioning
confidence: 99%
“…[9,12,13] A probiotic approach with the use of O. formigenes, Eubacterium lentum, Lactobacillus acidophilus and all other microorganisms is considered promising today. [14,15] A substantial body of research has been conducted on the ability of probiotics to reduce oxalate excretion. These studies have led to promising, but, all in all, ambiguous results requiring confirmation with the help of larger, welldesigned randomized clinical trials.…”
Section: Primary Hyperoxaluria: (≥1 µMol/d) It Is Characterized Bymentioning
confidence: 99%